The Effect of Managerial Ownership and Tax Avoidance On Firm Value With Firm Transparency as a Moderating Variable - Putri, Novita Winda Crisdiana; Ardhani, Lutfi (Akuisisi : Jurnal Akuntansi, 2023)
PThis research was conducted with the aim of knowing the effect of Managerial Ownership and also Tax Avoidance with company transparency as a moderating variable in companies listed in the beverage subsector. This research is a descriptive quantitative study that uses secondary data in the form of financial statements of companies in the food and beverage sub-sector manufacturing sector listed on IDX. A sample of 11 companies was used which was obtained by purposive sampling technique. The data analysis technique used in this research is MRA or Moderated Regression Analysis which is processed using SPSS tools. The results show that managerial ownership and tax avoidance have a significant positive effect on firm value. Meanwhile, managerial ownership of tax avoidance also has a significant positive effect on firm value with corporate transparency as a moderating variable